Stres Akademik Pasca Pandemi Covid-19: Resiliensi Dan Motivasi Akademik Serta Usia Sebagai Variabel Moderator - Pantu, Eka (Psikodinamika: Jurnal Literasi Psikologi, 2024)
The end of the Covid-19 pandemic apparently did not make students' academic stress levels return to normal. Two factors that influence academic stress are resilience and academic motivation. Apart from that, the age factor is also suspected to be a moderator variable in the influence of academic motivation on academic stress. This research aims to determine the role of resilience and academic motivation on academic stress and how age is a moderator variable in the influence of academic motivation on academic stress. The subjects in this research were 272 students from universities in Gorontalo. The measuring instruments used in this research are the academic stress perception scale from Bedewy and Gabriel (2015), the short resilience scale developed by Smith, Dalen, Wiggins, Tooley, Christopher, and Bernard (2008), and the academic motivation scale from Natalya (2018). Data analysis shows that resilience (ꞵ= -0.264, p= <0.001) and academic motivation (ꞵ= 0.164, p= 0.007) influence academic stress. It was also found that age was a moderator in the influence of academic motivation on academic stress (ꞵ= 0.768, p=0.022)